Aetiology of molar-incisor hypomineralisation (MIH) in Brazilian children - Souza, J. F. [UNESP]; Jeremias, F. [UNESP]; Costa-Silva, C. M.; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Zuanon, Angela Cristina Cilense [UNESP]; Cordeiro, Rita de Cássia Loiola [UNESP] (Springer Nature, 2013)
Aim: To determine the potential aetiological factors related to molar-incisor hypomineralisation (MIH) in Brazilian children. Methods: A total of 1,151 children aged 7-12 years (mean 8.86 ± 1.28), born and living in the urban area of Araraquara, Brazil, were examined by two examiners evaluating the presence of MIH according to criteria suggested by the European Academy of Paediatric Dentistry (2003). Their mothers completed a structured questionnaire about medical history, from pregnancy to the first 3 years of the children's life. Descriptive analyses of data and odds ratios (OR) with 95 % test-based confidence intervals (CI) were estimated. Chi-square test was used to evaluate the differences between groups. Results: The prevalence of MIH in the children was 12.3 %. The interviewing response rate was 90.4 %. The prevalence of miscarriage history (25 vs. 15.4 %; OR = 1.21; 95 % CI 0.30-4.92) and occurrence of anaemia (23 vs. 12.4 %; OR = 2.07; 95 % CI 0.50-8.63) were higher in mothers from MIH group than those from non-MIH group. However, these associations were not statically significant. In the children's medical history, rhinitis, bronchitis (56.5 vs. 52.5 %; OR = 1.17; 95 % CI 0.82-1.68), and high fever (20.4 vs. 18.2 %; OR = 1.14; 0.73-1.76) were more prevalent in MIH group, but there were no significant differences between the groups (p > 0.05). Conclusions: No possible aetiological factor investigated was associated with MIH. Prospective studies are needed to define the aetiological factors involved with MIH. © 2013 European Academy of Paediatric Dentistry.
Keywords: Aetiology; Epidemiology; Molar-incisor hypomineralisation